Characterization of sheep carcasses in the Costa Rican market for the generation of a visual classification scale - Montero-Salas, Daniela (2021)
Every day, the national sheep sector is in search of improving the quality of meat produced, however, in this industry there is no standard classification system for sheep carcasses in the country. The objective of this work was to evaluate the morphometric characteristics of sheep carcasses in order to generate a practical visual tool that allows the conceptualization of a standardized commercial carcass model for the Costa Rican market. The investigation took place between January and December 2019, in three sheep processing plants, located in Las Nubes de Coronado, Balsa de Atenas and Miramar de Puntarenas, Costa Rica. Ninety five carcasses of different breeds, ages and origins were sampled, measuring live weight, hot carcass, carcass performance, sex, dental age, muscular conformation, thickness of back fat in hot and cold carcasses, and fat coverage. Meat samples and photographs were taken for analysis. On average, the carcasses had a live weight of 38.3kg, the hot carcass weighed 17.2kg, the yield was 45% and the subcutaneous fat thickness was 7.1mm. When quantifying color with the CIELab scale, averages of 40.57 (L*), 13.12 (a*) and 17.32 (b*) were obtained. When associating age with the results, a low negative correlation was obtained for L* (r=-0.32) and b* (r=-0.215), and a low positive correlation for a * (r=0.04). The difference between the thickness of the fat in hot and cold carcasses in 18.9% of the total carcasses was 0.18cm on average. Then a linear regression was performed (R2=0.79); however, the sample is small.  A visual tool made up of three dimensions was proposed using the hot carcass, thickness and fat coverage, consisting of a guide to improve the final product and as a standardized model of carcasses for exportation.